Teaching Students the Spanish Language in the context of the cultural approach (topic «Las Navidades») - О. Б. Бігич (Іноземні мови, 2015)
The methodological aspect of forming linguosociocultural competence in the context of cultural approach of teaching students the Spanish language (by example of the topic “Las Navidades”) is represented in the article. Here is represented the Spanish language lesson agenda made by the authoress. Methodological guidelines for the organization of extra curricular activities are introduced above.